Latency-Aware Rate Adaptation in 802.11n Home Networks - Li, Chi-Yu; Tu, Guan-Hua; Lu, Songwu; Wang, Xinbing; Chandra, Ranveer (IEEE Infocom, 2015)
Latency-sensitive applications (e.g., wireless gaming and TV remote play) are increasingly popular in home Wi-Fi networks. Such millisecond-level latency requirements call for new ﬁne-grained approaches at the link layer. In this paper, we show that current solutions work well for throughput but not for latency due to the long tail of the packet delay distribution. We thus propose LLRA, a new latency-aware rate adaptation scheme that reduces the tail latency for delay-sensitive applications. LLRA takes concerted design in rate control, frame aggregation scheduling and software/hardware retransmission dispatching. Our implementation and evaluation conﬁrm the viability of LLRA in 802.11n home networks.